The Effect of Green Laser on Human White Blood Cells - Abdullah, Manar Nazim; Ahmed Ali, Tamara; saeed, Huda Nizar Muhammad; Hazim, Alaa Ghanem; Abdullah, Raghad Saad Yousef (American Journal of Botany and Bioengineering, 2024)
This graduation project investigates the effect of green laser light with a wavelength of 532 nanometers on the shape and size of human white blood cells. The study utilized samples of blood from adult male and female humans as models. Ten samples were prepared, consisting of 5 samples from males and 5 from females. Each sample was exposed to the laser for periods ranging from 0 to 20 minutes, with 5-minute intervals, resulting in varying doses received by the samples. The results showed that the external shape and size of white blood cells depend on the laser dose used, suggesting biological and chemical changes occurring in response to the applied laser doses.